Augmented reality application centered on the child as a resource in a virtual learning environment - Francisco Gabriel Bezares Molina; Guadalupe Toledo Toledo; Francisco Aguilar Acevedo; Eduardo Martínez Mendoza (Universidad de Guadalajara, 2020)
Given its characteristics, augmented reality (AR) is presented as an alternative resource in a virtual learning environment (VLE) by providing virtual elements in the real world, which can facilitate learning. This article aims to describe the development of a mobile application with guided AR under the fundamentals of UserCentered Design (UCD) in order to be integrated into a VLE. The development strategy consisted of using the UCD and in its phases making use of tools such as: surveys for the collection of information, Quality Function Deployment to identify and prioritize requirements, AR technology for prototyping and finally usability tests to identify design problems. As a result, it was possible to demonstrate the viability of this procedure in the development of interfaces of this type, considering that the resources that contextualize the needs and tastes of its users can provide better facilities and motivation within their learning. The case study studied is that of English for primary school children, which allowed verifying that this detailed framework can be replicated to other areas of interest and allow teachers to integrate AR applications in face-toface or online learning environments.